Dental biofilm acidogenicity induced by pediatric oral medications: a double-blind randomized clinical trial - Karla Pinheiro de Alencar; Daniel Fernandes Peixoto; Fábio do Nascimento Máximo; Isabela Albuquerque Passos Farias; Fábio Correia Sampaio (Brazilian Oral Research)
Abstract The aim of this study was to evaluate in vivo dental biofilm acidogenicity induced by nine long-term pediatric oral liquid medications (OLMs). A double-blind crossover randomized clinical trial was conducted with 12 individuals aged 18 to 22 years who had good oral hygiene (OSI < 1.1) and a DMFT index of less than 12. Each participant was exposed to nine OLMs and a 10% sucrose solution (positive control) as part of the crossover design. The pH of the dental biofilm was measured with a Beetrode® microelectrode at 0, 5, 10, 15, 20, 25, and 30 min. Statistical analysis was performed to determine the minimum pH and the area under the curve (AUC). One-way ANOVA was utilized, and the significance level was set at 0.05. Pediatric OLMs caused a sucrose-like decrease in biofilm pH, regardless of therapeutic class (p > 0.05). The mean ± standard deviation of the AUC ranged from 16.26 ± 11.59 (cetirizine) to 39.22 ± 20.81 (azithromycin), with no statistically significant difference compared to sucrose (25.22 ± 6.97) (p > 0.05). The findings suggest that pediatric OLMs contribute to dental biofilm acidogenicity, with a more pronounced effect induced by medications used for respiratory diseases and also by antibiotics.